ANALYSIS OF MUSIC ART LEARNING ON MATERIAL RECOGNIZING THE SHAPE AND SOUND OF MUSICAL INSTRUMENTS IN ELEMENTARY SCHOOLS - Lestari, Dinda Rizki (Program Studi PGMI, 2024)
Analysis of music art learning on material recognizing the shape and sound of musical in-struments in elementary schools aims to find out how the implementation of learning recog-nizes the shape and distinguishes the sound of musical instruments in elementary schools. The research method used is qualitative descriptive. Data collection techniques use inter-views, observation, and documentation. Data analysis through data reduction, data presen-tation and conclusion. From the results of the analysis, it was obtained that learning to rec-ognize the shape and sound of musical instruments in elementary schools was seen from the following 7 things, namely: 1) There are two attitudes shown by students, namely a positive attitude and a negative attitude; 2) The teacher does not have the ability to play a musical in-strument; 3) Learning planning is carried out by preparing a learning implementation plan (RPP); 4) The learning methods used vary and can motivate students; 5) Teaching materials used in the form of student books, student handbooks, and LKS; 6) The learning media used is still sober and not in accordance with the objectives and learning materials; and 7) Learning evaluation only measures aspects of knowledge, without measur-ing aspects of attitudes and skills.